2020
DOI: 10.1021/acs.jced.9b00945
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4-Based Melamine-Rich Covalent Organic Polymer for Simultaneous Removal of Auramine O and Rhodamine B

Abstract: The present study focused on utilizing the advantages of porous covalent organic frameworks by preparing them in a usable magnetite support form with Fe 3 O 4 nanoparticles using the solvothermal method. Functionalized Fe 3 O 4 -based melamine-rich covalent organic polymer (COP) was prepared and identified using different physicochemical techniques, such as Fourier-transform infrared, X-ray diffraction, field emission scanning electron microscopy, Brunauer−Emmett−Teller analysis, and vibrating sample magnetome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…With the increase in synthesis and production of Fe-oxide NPs over the last 30 years, their release to the environment is inevitable and cycle regeneration must be carried out to control their liberation and reuse for diverse applications. Some works have reported the regeneration of magnetic NPs, for example, that of Shakeri et al [ 131 ], who reported the regeneration protocol for the Fe 3 O 4 -based melamine-rich covalent organic polymer used for the removal of Auramine O (AO) and Rhodamine B (RB). The ethanol extraction technique was performed on the Fe-oxide NPs under nine cycles and the removal efficiency was 95% for AO and 88% for RB, suggesting the potential removal character of the Fe-oxide NPs.…”
Section: In-detail Discussion Of the Adsorbent Propertiesmentioning
confidence: 99%
“…With the increase in synthesis and production of Fe-oxide NPs over the last 30 years, their release to the environment is inevitable and cycle regeneration must be carried out to control their liberation and reuse for diverse applications. Some works have reported the regeneration of magnetic NPs, for example, that of Shakeri et al [ 131 ], who reported the regeneration protocol for the Fe 3 O 4 -based melamine-rich covalent organic polymer used for the removal of Auramine O (AO) and Rhodamine B (RB). The ethanol extraction technique was performed on the Fe-oxide NPs under nine cycles and the removal efficiency was 95% for AO and 88% for RB, suggesting the potential removal character of the Fe-oxide NPs.…”
Section: In-detail Discussion Of the Adsorbent Propertiesmentioning
confidence: 99%
“…Recently, Rafiee and co-workers fabricated a melamine-rich magnetic covalent organic polymer (MCOP) for the removal of AO and RB. 147 removal of AO and RB. The presence of free lone pair electron in various imine groups present on Fe 3 O 4 /C-COP could electrostatically interact with cationic RB and AO, which enhanced the adsorption behaviour.…”
Section: Aromatic Dyes Removalmentioning
confidence: 99%
“…Recently, Rafiee and co-workers fabricated a melamine-rich magnetic covalent organic polymer (MCOP) for the removal of AO and RB. 147…”
Section: Aromatic Dyes Removalmentioning
confidence: 99%
“…By use of adsorption kinetics models were investigated the mechanism and rate-determining step. 58,59 Obtained data was fitted with pseudo-first-order and pseudo-second-order kinetics models (Figure 6) and kinetic parameters summered in Table 7. These results…”
Section: Adsorption Kinetics Studiesmentioning
confidence: 99%